EVALUASI PENYELENGGARAAN PROGRAM PELATIHAN TATA BOGA MENGGUNAKAN MODEL CIPPO DI SPNF SKB UNGARAN - Salma Aulia Fitriyani; Muarifuddin Muarifuddin (Jurnal Manajemen Pendidikan, 2026)
This study evaluates the culinary training program at SPNF SKB Ungaran using the CIPPO (Context, Input, Process, Product, Outcome) evaluation model. A qualitative evaluative approach was employed, involving the head of the institution, program managers, instructors, and two alumni selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive data analysis model. The findings reveal that the program is aligned with community needs and local economic potential, particularly in supporting micro-scale culinary entrepreneurship. The input component demonstrates adequate instructor qualifications, sufficient learning facilities, and a needs-based curriculum design. The learning process emphasizes practical activities (80%) over theoretical instruction (20%), contributing to significant improvements in participants' technical competencies and self-confidence. The product evaluation indicates enhanced cognitive, psychomotor, and affective competencies. At the outcome level, interviewed alumni have successfully developed independent culinary businesses, reflecting positive economic empowerment. This study contributes by applying the CIPPO model to evaluate nonformal vocational training programs at SKB, with emphasis on long-term entrepreneurial outcomes within life skills education framework.